The Role of Exporters’ Emotional Intelligence in Building Foreign Customer Relationships - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Zeriti, Athina; Christodoulides, Paul (My University, 2019)
Despite the critical importance of emotional intelligence in effectively interacting with other people, its role has been overlooked in scholarly research on cross-border interorganizational relationships. Drawing on emotion regulation theory, the authors propose a model that conceptualizes links among exporters’ emotional intelligence, key behavioral dimensions characterizing the atmosphere of the relationship with import buyers, and the resulting relational performance. They test the model with data collected from 262 Greek exporters using structural equation modeling. The results indicate that higher levels of exporter emotional intelligence enhance communication and social bonding with the importer while diminishing distance and conflict in their working relationship. Relational performance is positively influenced by communication and social bonding but negatively affected by distance and conflict. The results also reveal the moderating effect of both opportunism and interpartner incompatibility on the association between the exporter’s emotional intelligence and the behavioral atmosphere of the relationship with import buyers.
Keywords: Emotional intelligence; Relational performance; Exporting; Business relationships